Bronchial asthma in children aged 7-14 years depending on its treatment and control - I. K. Bogomolova; M. P. Bryzgalin; A. A. Pohodenko (Кубанский научный медицинский вестник, 2014)
Bronchial asthma in children aged 7-14 years has mild and middle forms without any sex differences. When the course of this disease increases the gravity of pathologic process worsens. Positive control in treatment of this disease reached 48,39% of cases only in mild and mean grave cases. In 41,49% of children a part of good results in treatment of bronchial asthma was achieved. In 43,55% of cases basic therapy was not fully carried out or was performed only in exacerbation of bronchial asthma.